Pengaruh Digital Komik Berbasis Realistic Mathematic Education Terhadap Kemampuan Pemecahan Masalah - Yunisyah Hasyanah; Novika Sukmaningthias; Novita Sari; Zuli Nuraeni (Universitas Islam Ahmad Dahlan (UIAD) Sinjai, 2023)
The ability to solve mathematical problems is an ability that needs to be mastered by students. However, in fact the ability of students' mathematical problem solving is relatively low. This is caused by one of them using inappropriate learning media. Therefore we need learning media that can help students to practice their mathematical problem solving abilities. The media in question is digital comics based on realistic mathematics education (RME). So the purpose of this study was to look at the effect of digital comics based on realistic mathematics education (RME) on students' mathematical problem solving abilities. The research method used is a quasi-experimental method using The Pretest-Posttest Non-Equivalent Control Group design. The results of statistical analysis obtained Sig. (2-tailed) in the output equal variances not assumed 0.000, where the value of Sig. (2-tailed) obtained is less than 0.05 or it can be said that 0.000 <0.05. So, based on the decision-making results of the analysis of this hypothesis test, it can be concluded that if